Empirical Evidence of the Impact of Equity Market Volatility on Government and Corporate Bond Yields and Yields Spreads - the case of South Korea - Mahgoub, Ghadir Kamaleldin Ali (2015)
In this study we employ time series data of daily changes in South Korean one-year Government and corporate bond indexes yields dated from January 4, 2010 to December 31, 2013 to examine the effect of future or implied and realized or contemporaneous equity market volatility on the yields and yield spreads. The VKOSPI index is our measure if implied future volatility, while we construct the measure of contemporaneous or realized volatility by employing minute-to-minute KOSPI 200 returns. We observe that in general, bond yields and yield spreads